Interference of English Vowels by Dawan (Amarasi Dialect) Speakers - Maya Romanti Amtiran; Adi Sutrisno (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates the types of English vowel interference produced by ten native speakers of Dawan language (Amarasi dialect) using an acoustic phonetic approach. The participants were recorded producing English words containing nine target vowels (/iː/, /ɪ/, /ɛ/, /æ/, /ʌ/, /ɑː/, / ɔː/, /uː/, and /u/) The formant frequencies (F1 and F2) were analyzed using Praat software to identify deviations from English vowels and classify the types of interference. The analysis revealed three primary interference types: substitution, under-differentiation and reinterpretation. Substitution interference involved replacing English vowels /æ/ → [a] and /ɔː/ → [o]. Under-differentiation occurred when speakers failed to distinguish English phonemic contrasts in vowels /iː/→[ɪ] and /ʌ/ → [ɑː]. Reinterpretation was observed in fronted or centralized realizations of back vowels, such as /uː/ → [ʉ] or [y]. Vowel space contraction and centralization were found in both English target and informant products, indicating Dawan vowel characteristics impact English pronunciation. These results highlight that L1 phonology strongly affects L2 vowel production and propose vowel contrast awareness pronunciation training.